IMPLEMENTASI PERSAINGAN USAHA TIDAK SEHAT JASA TRANSPORTASI DI BANDARA SULTAN SYARIF KASIM II PEKANBARU - Darmawanto, Setia; ', Firdaus; Fitriani, Riska (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Transport has an important role to stabilize embodiment archipelago insight, improve the wheels of the economy, strengthen national security, and strengthen the relationships between nations in order to achieve national objectives, one of which is air transport. Competence is a condition that is always close to human characteristics, which man always has a tendency to outperform each other humans in many ways. business competition law is the law governing the interaction of companies or businesses in the market, while the company's behavior based on economic motives. Talking about the business copetition, constitution No. 5 of 1999 has been set About Prohibition of Monopolistic Practices and Unfair Business Competition. The author uses a kind of sociological research is research on the effectiveness of the law in force or a study of the legal identification of the location where the research was conducted at PT. AngkasaPura 2, PT. Blue Bird Group, Puskopau and KopsiPekanbaru. In collecting data for sociological research the author uses premier data sources and secondary data, data collection tools that I use in this study is observation, interviews and a literature review. The conclusion that can be found in the implementation of unfair competition is happening at the airport Sultan SyarifKasim II Pekanbaru not correspond Law - No. 5 of 1999 concerning Prohibition of Monopolistic Practices and Unfair Competition and impacts that occur as a result of unfair competition going on Sultan SyarifKasim II Airport Pekanbaru form of impact for businesses and consumers as well as suggestions from the authors is the celestial temple II Pekanbaru should be able to run the KPPU decision Case No.27 / KPPU-L / XII / 2007 on discrimination taxi service at Sultan SyarifKasimPekanbaru in order to create fair competition between businesses taxi transportation services.Keywords: Implementation - Business Competence - Competition - Services - Transport.